Can AI Improve Melanoma Detection Accuracy? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2018)
Melanoma, the most aggressive form of skin cancer, poses a significant global health challenge. Early and accurate detection is paramount to improving patien...
Keywords: AI in Dermatology; Improve; Melanoma; Detection; Artificial Intelligence; Deep Learning